Surrogate markers of infection: Interrogation of the immune system - Chakera, Aron; Lucas, A.; Lucas, M. (2011)
Infectious diseases remain the greatest causes of morbidity and mortality in global terms. As much of the burden occurs in the developing world, limited access to diagnostic testing has hampered the diagnosis and treatment of these conditions, while, in the developed world, the cost of managing infectious diseases remains considerable. Despite the size of the problem there remains an ongoing need for tests that improve diagnostic sensitivity and specificity, provide more rapid diagnoses, are available for point-of-care testing in remote regions, and can help inform therapeutic decision-making by identifying resistance patterns or patient outcomes. This article discusses the background to biomarker development for infectious diseases, some current assays that are providing useful information regarding the host's response to infection (using examples such as Cytomegalovirus and Mycobacterium tuberculosis), as well as likely future technologies and their limitations. © 2011 Future Medicine Ltd.